Heat Acclimation-Mediated Cross-Tolerance: Origins in within-Life Epigenetics? - Horowitz, Michal (Frontiers in Physiology, 2017)
The primary outcome of heat-acclimation is increased thermotolerance, which stems from enhancement of innate cytoprotective pathways. These pathways produce “ON CALL” molecules that can combat stressors to which the body has never been exposed via cross-tolerance mechanisms (heat acclimation-mediated cross-tolerance - HACT). The foundation of HACT is the sharing of generic stress signaling combined with tissue/organ specific protective responses. HACT becomes apparent when acclimatory homeostasis is achieved; lasts for several weeks and has a memory. HACT differs from other forms of temporal protective mechanisms activated by exposure to lower "doses" of the stressor, which induce adaptation to higher doses, e.g. preconditioning, hormesis. These terms have been adopted by biochemists, toxicologists, and physiologists to describe the rapid cellular strategy ensuring homeostasis. HACT employs two major protective avenues: constitutive injury-attenuation and abrupt post insult release of help signals enhanced by acclimation. To-date, the injury-attenuating features, in all organs studied; include fast-responding enlarged cytoprotective reserves with HSPs, anti-oxidative, anti-apoptotic molecules, and HIF-1 nuclear and mitochondrial target gene products. Using cardiac ischemia and brain hypoxia models as a guide to the broader framework of phenotypic plasticity, HACT, is enabled by a metabolic shift induced by HIF-1 and there are less injuries caused by Ca+2 overload, via channel or complex-protein remodeling or decreased channel abundance. Epigenetic markers such as posttranslational histone modification and altered levels of chromatin modifiers during acclimation and its decline suggest that dynamic epigenetic mechanisms controlling gene expression induce HACT and acclimation memory to enable the rapid return of the protected phenotype.